2019
DOI: 10.1097/mcg.0000000000001143
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a Defecation Posture Modification Device

Abstract: Goals: The goal of this study was to evaluate the influence of defecation postural modification devices (DPMDs) on normal bowel patterns. Background: The introduction of DPMDs has brought increased awareness to bowel habits in western populations. Materials and Methods: A prospective crossover study of volunteers was performed that included real-time collection of data regarding bowel movements (BMs) for 4 weeks (first 2 wk without DPMD and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…This position should be reached on the toilet by placing a support under the feet. This avoids pushing and, thus, increases pressure in the intra-abdominal cavity, lowering the PFM and weakening them [74]. The toilet should be used at the same time, as the nervous system is then accustomed to regularity.…”
Section: Prevention Of Fecal Incontinencementioning
confidence: 99%
“…This position should be reached on the toilet by placing a support under the feet. This avoids pushing and, thus, increases pressure in the intra-abdominal cavity, lowering the PFM and weakening them [74]. The toilet should be used at the same time, as the nervous system is then accustomed to regularity.…”
Section: Prevention Of Fecal Incontinencementioning
confidence: 99%
“…This theory led to the use of a 'Defecation Posture Modi cation Device' (DPMD) with the seating type of toilet. The DPMD brings the hips and knees in a pseudo-squatting position thus facilitates relaxation of the pelvic oor muscles during defecation [16]. It was also reported that the squatting action during use of squatting toilets improved blood ow velocity in the lower extremities [17], and the user is subjected to squatting, as a form of exercise for strengthening of the quadriceps muscles.…”
Section: Resultsmentioning
confidence: 99%
“…The DPMD brings the hips and knees in a pseudo-squatting position thus facilitates relaxation of the pelvic floor muscles during defecation. 16 It was also reported that the squatting action during use of squatting toilets improved blood flow velocity in the lower extremities, 17 and the user is subjected to squatting, as a form of exercise for strengthening of the quadriceps muscles. Quadriceps strength is associated with a lower cardiovascular mortality in patients with coronary artery disease.…”
Section: Discussionmentioning
confidence: 99%